Scoliosis In Young Athletes: Influence of Gymnastic Training and Screening Strategies - Dziegciarczyk, Anna; Wiater, Zuzanna; Włodarczyk, Aleksandra; Swoboda, Kamil; Brankowska, Karolina; Kuryłek, Michał; Dziegciarczyk, Andrzej; Banyś, Filip; Polakowska, Anna; Pyzik, Alicja; Jakubowska, Marta (Quality in Sport, 2026)
Objective. This review aims to evaluate the prevalence of scoliosis among young athletes, specifically focusing on the biomechanical influence of gymnastic training and the efficacy of various screening strategies for early detection. Methods. A comprehensive analysis of recent literature and clinical studies (including rhythmic, artistic, and acrobatic gymnastics) was conducted. The review synthesizes data on epidemiological trends, training-related risk factors, and diagnostic accuracy of non-invasive screening tools. Results. Research indicates that young gymnasts exhibit a significantly higher prevalence of scoliosis compared to the general population, with "scoliosis suspected status" reaching approximately 28.8% in competitive cohorts. The etiology is multifaceted, often described through the "dangerous triad" of generalized joint hyperlaxity, delayed skeletal maturity, and asymmetric mechanical loading. High training volumes—exceeding 22–26 hours per week—and the repetitive execution of spinal hyperextension elements ("the arch") are identified as primary contributors to sagittal curvature alterations and overuse injuries. However, active sports participation, when properly monitored, can also play a protective role in reducing curve progression. Effective screening remains the cornerstone of management; the Adam’s Forward Bend Test (AFBT) combined with scoliometer measurements (ATR) and modern 3D surface topography (ST) provides a reliable, radiation-free framework for monitoring athletes during the critical growth period of 10–15 years. Conclusion. Young gymnasts represent a high-risk group for the development of spinal deformities. Integrating standardized, non-invasive screening protocols into routine pre-participation physical evaluations (PPE) is essential for early diagnosis and the success of conservative treatment strategies, ensuring the long-term musculoskeletal health of adolescent athletes.